Long-term Use of Saline Drainage Waters for Irrigation in Subsurface Drained Lands: Simulation Modelling with SWAP - Verma, A K; Gupta, S K; Isaac, R K (Journal of Agricultural Engineering, 2010)
SWAP (Soil-Water-Atmosphere-Plant) version 2.0 was evaluated for its capability to simulate crop growth and salinity profiles for a saline water irrigated area (Sampla, District Rohtak, Haryana) having shallow water table provided with a subsurface drainage system. Canal water (0.7 dS.m?¹) was used for pre-sowing irrigation in all the treatments and thereafter, canal (0.7 dS.m?¹), mixed canal and saline drainage water of varying salinity (6, 9, 12 dS.m?¹) and drainage water alone varying in salinity from 12 to 27 dS.m?¹ were used for irrigation. Absolute deviations and standard error between the SWAP simulated and the observed relative yields during calibration ranged from 2.6 to 7.2% and 3.1 to 9.7%, respectively, and established the validity of SWAP model under the experimental conditions. The scenario building simulations carried out with the validated SWAP revealed that yield at a higher level could be sustained with subsurface drainage than without it. Optimum yields in most years could be obtained with irrigation water of EC dS.m?¹. It was established that notwithstanding the seasonal build-up of salts due to saline water use, there would be no long-term build-up of salts as leaching during the monsoon season would render the soil profile salt free at the time of sowing of rabi crops. SWAP was found to be a useful tool to assess the performance of subsurface drainage systems with reuse of saline drainage water for crop production.